Investigating the Impact of Structural Features on F1 Car Diffuser Performance Using Computational Fluid Dynamics (CFD) - Eugeni Pérez Nebot; Antim Gupta; Mahak Mahak (Mathematics)
This study utilizes Computational Fluid Dynamics (CFD) to optimize the aerodynamic performance of a Formula 1 (F1) car diffuser, investigating the effects of vane placements, end-flap positions, and other structural modifications. Diffusers are critical in managing airflow, enhancing downforce, and reducing drag, directly influencing vehicle stability and speed. Despite ongoing advancements, the interaction between diffuser designs and turbulent flow dynamics requires further exploration. A Three-Dimensional k-Omega-SST RANS-based CFD methodology was developed to evaluate the aerodynamic performance of various diffuser configurations using Star CCM+. The findings reveal that adding lateral vane parallel to the divergence section improved high-intensity fluid flow distribution within the main channel, achieving 13.49% increment in downforce and 5.58% reduction in drag compared to the baseline simulation. However, incorporating an airfoil cross-section flap parallel to the divergence end significantly enhances the car’s performance, leading to a substantial improvement in downforce while relatively small increase in drag force. This underscores the critical importance of precise flap positioning for optimizing aerodynamic efficiency. Additionally, the influence of adding flaps underneath the divergence section was also analyzed to manipulate boundary layer separation to achieve improved performance by producing additional downforce. This research emphasizes the critical role of vortex management in preventing flow detachment and improving diffuser efficiency. The findings offer valuable insights for potential FIA F1 2023 undertray regulation changes, with implications for faster lap times and heightened competitiveness in motorsports.